NOX5: from basic biology to signaling and disease - Bedard, Karen; Jaquet, Vincent; Krause, Karl-Heinz (Free radical biology & medicine, 2012)
In mammals, the NADPH oxidase family of enzymes comprises seven members: NOXs 1–5, DUOX1, and DUOX2. All of these enzymes function to move an electron across cellular membranes, transferring it to oxygen to generate the superoxide anion. This generation of reactive oxygen species has important physiological and pathophysiological roles. NOX5 is perhaps the least well understood of these NOX isoforms, in part because the gene is not present in mice or rats. In recent years, however, there has been a rapid increase in our understanding of the NOX5 gene, the structural and biochemical aspects of the NOX5 enzyme, the role NOX5 plays in health and disease, and the development of novel NOX inhibitors. This review takes a look back at some historical aspects of the discovery of NOX5 and summarizes our current understanding of the enzyme. ► NOX5 is a member of the NOX NADPH family of enzymes. ► It generates superoxide in response to elevated calcium. ► Here we review aspects of the NOX5 gene and its role in health and disease and discuss NOX5 inhibitors.